Schritt um Schritt die Entwicklung des Kindes bis ins 7. Lebensjahr - Grauel, Ernst Ludwig 1935-2005; Schmidt, Hans-Dieter 1927-2007; Schneeweiß, Burkhard 1931-; Grauel, Ernst Ludwig 1935-2005 (Berlin Verl. Volk und Gesundheit, 1989)
Literaturverz.
Literaturverz